DESIGN AND DEVELOPMENT OF WEB-BASED PRODUCTION SCHEDULING APPLICATION IN CV. REMAJA DUA - Luky Rahman; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
CV Remaja Dua is a company in the field of convection. The problem that exists today is that this company only accepts orders as much as 3000 clothes per month, the rest of the company does not accept the work of clothes again. While the capacity of machines and employees can work up to 3536 clothes per month. This is because the company has not optimized the performance of production employees. Another problem is the lack of good production scheduling so companies often experience delays to complete the order. Based on data obtained from 40 orders per month there are 15 orders that are late or about 37% of orders are late in the process. With the existence of the problem, then owner of CV. Remaja Dua wants a production scheduling app that can be used to minimize the delay of the finished time of the order and optimize the performance of production employees. The results of the trial and evaluation conducted, showed that the Design of Production Scheduling Applications at CV Ramaja Dua produces production schedules and distribution of workmanship in accordance with the capacity of each employee. In addition, applications can also increase the maximum number of orders up to 35% of the total maximum orders received each month.